BENTUK PEMERTAHANAN BAHASA GAYO DALAM PEMBELAJARAN MUATAN LOKAL - Annisa Khalila; Alfi Syahrin; Wirdatul Isnani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The decline in Gayo language usage among the younger generation—driven by the dominance of Indonesian, technological advancements, and reduced use of the regional language within families—poses a threat to the language's survival. Consequently, efforts to preserve the language through local content curricula in schools are essential. This study aims to describe the forms of Gayo language preservation within the local content curriculum for 7 th-grade students at SMP Terpadu Alazhar and to identify factors hindering its implementation. A qualitative approach using a descriptive method was employed. Data were gathered through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion-drawing techniques. The findings reveal five forms of Gayo language preservation: Gayo language local content instruction, school support, government support, cultural arts preservation, and the utilization of local wisdom. Additionally, eleven factors hindering implementation were identified, including limited Gayo language use in the family environment, the dominance of Indonesian, low student interest and confidence, the use of mixed languages, limited comprehension, and a lack of teaching materials and media. The study concludes that local content curricula play a vital role in preserving the Gayo language but require support from families, schools, and the government.